Developing an intervention around referral and admissions to intensive care: a mixed-methods study - Chris Bassford; Frances Griffiths; Mia Svantesson; Mandy Ryan; Nicolas Krucien; Jeremy Dale; Sophie Rees; Karen Rees; Agnieszka Ignatowicz; Helen Parsons; Nadine Flowers; Zoe Fritz; et al. (National Institute for Health Research, 2019)
Background: Intensive care treatment can be life-saving, but it is invasive and distressing for patients receiving it and it is not always successful. Deciding whether or not a patient will benefit from intensive care is a difficult clinical and ethical challenge. Objectives: To explore the decision-making process for referral and admission to the intensive care unit and to develop and test an intervention to improve it. Methods: A mixed-methods study comprising (1) two systematic reviews investigating the factors associated with decisions to admit patients to the intensive care unit and the experiences of clinicians, patients and families; (2) observation of decisions and interviews with intensive care unit doctors, referring doctors, and patients and families in six NHS trusts in the Midlands, UK; (3) a choice experiment survey distributed to UK intensive care unit consultants and critical care outreach nurses, eliciting their preferences for factors used in decision-making for intensive care unit admission; (4) development of a decision-support intervention informed by the previous work streams, including an ethical framework for decision-making and supporting referral and decision-support forms and patient and family information leaflets. Implementation feasibility was tested in three NHS trusts; (5) development and testing of a tool to evaluate the ethical quality of decision-making related to intensive care unit admission, based on the assessment of patient records. The tool was tested for inter-rater and intersite reliability in 120 patient records. Results: Influences on decision-making identified in the systematic review and ethnographic study included age, presence of chronic illness, functional status, presence of a do not attempt cardiopulmonary resuscitation order, referring specialty, referrer seniority and intensive care unit bed availability. Intensive care unit doctors used a gestalt assessment of the patient when making decisions. The choice experiment showed that age was the most important factor in consultants' and critical care outreach nurses' preferences for admission. The ethnographic study illuminated the complexity of the decision-making process, and the importance of interprofessional relationships and good communication between teams and with patients and families. Doctors found it difficult to articulate and balance the benefits and burdens of intensive care unit treatment for a patient. There was low uptake of the decision-support intervention, although doctors who used it noted that it improved articulation of reasons for decisions and communication with patients. Limitations: Limitations existed in each of the component studies; for example, we had difficulty recruiting patients and families in our qualitative work. However, the project benefited from a mixed-method approach that mitigated the potential limitations of the component studies. Conclusions: Decision-making surrounding referral and admission to the intensive care unit is complex. This study has provided evidence and resources to help clinicians and organisations aiming to improve the decision-making for and, ultimately, the care of critically ill patients. Future work: Further research is needed into decision-making practices, particularly in how best to engage with patients and families during the decision process. The development and evaluation of training for clinicians involved in these decisions should be a priority for future work. Study registration: The systematic reviews of this study are registered as PROSPERO CRD42016039054, CRD42015019711 and CRD42015019714. Funding: The National Institute for Health Research Health Services and Delivery Research programme. The University of Aberdeen and the Chief Scientist Office of the Scottish Government Health and Social Care Directorates fund the Health Economics Research Unit.